Decisions about decisions : practical reason in ordinary life / Cass R. Sunstein. - Sunstein, Cass R. (Cambridge University Press, 2023)
Here is one of the most fundamental questions in human life: How do we decide how we decide? We make such decisions all the time. If you trust your doctor, you might decide to follow a simple rule for medical decisions: Do whatever your doctor suggests. If you like someone a lot, and maybe love them, but are not sure whether you want to marry them, you might do this: Live with them first. Some of these strategies are wise. They prevent error. They improve your emotional well-being. Some of these strategies are foolish. They lead you in the direction of terrible mistakes. They prevent you from learning. They might make you miserable. Decisions about Decisions explores how people do, and should, make decisions about decisions. It aims to see what such decisions are, to explore how they go right, and see where they go wrong.